Cerebral and muscle tissue oxygenation during incremental cycling in male adolescents measured by time-resolved near-infrared spectroscopy - Ganesan, G.; Leu, S. Y.; Cerussi, A.; Tromberg, B.; Cooper, D. M.; Galassetti, P. (Pediatric Exercise Science, 2016)
Near-infrared spectroscopy has long been used to measure tissue-specific O2 dynamics in exercise, but most published data have used continuous wave devices incapable of quantifying absolute Hemoglobin (Hb) concentrations. We used time-resolved near-infrared spectroscopy to study exercising muscle (Vastus Lateralis, VL) and prefrontal cortex (PFC) Hb oxygenation in 11 young males (15.3 ± 2.1 yrs) performing incremental cycling until exhaustion (peak VO2 = 42.7 ± 6.1 ml/min/kg, mean peak power = 181 ± 38 W). Time-resolved near-infrared spectroscopy measurements of reduced scattering (µs´) and absorption (µa) at three wavelengths (759, 796, and 833 nm) were used to calculate concentrations of oxyHb ([HbO2]), deoxy Hb ([HbR]), total Hb ([THb]), and O2 saturation (stO2). In PFC, significant increases were observed in both [HbO2] and [HbR] during intense exercise. PFC stO2% remained stable until 80% of total exercise time, then dropped (-2.95%, p = .0064). In VL, stO2% decreased until peak time (-6.8%, p = .01). Segmented linear regression identified thresholds for PFC [HbO2], [HbR], VL [THb]. There was a strong correlation between timing of second ventilatory threshold and decline in PFC [HbO2] (r = .84). These findings show that time-resolved near-infrared spectroscopy can be used to study physiological threshold phenomena in children during maximal exercise, providing insight into tissue specific hemodynamics and metabolism.